Analisa dan perancangan Marketplace Q-Store studi kasus tembilahan - Irwandi Rizki Putra; Muh. Rasyid Ridha (JURNAL PERANGKAT LUNAK, 2020)
Along with the times, technology and information are developing rapidly in various sectors in terms of human life. In the business world, technological development is very helpful in many ways. The phenomenon that occurs at this time is the increasingly widespread competition in the business world, especially in the field of marketplace in getting consumers to the emergence of various online marketplace sites. So far, Tembilahan online shop business is only known through social media such as Facebook, Whatsapp and Instagram or verbally to the public. Therefore, researchers are interested in taking a title, namely Marketpleace Q-Store Market Analysis and planning. Tembilahan Case Study aims to become a media promotion, and can make it easier for people to find goods that they want. In designing this Marketplace, the analysis used is PIECES and UML (Unified Modeling Language) as modeling and using the Framework code igniter to facilitate researchers in building systems. With the implementation of the Marketplace Q-Store, it provides a platform for seller to market their products.